Optimasi Koordinasi Rele Arus Lebih Menggunakan Metode Algortima Kunang Kunang Pada Penyulang Pantry Gardu Induk Cipinang - Muhammad Rizky Kurniawan; Hasna Satya Dini (Sekolah Tinggi Teknik - PLN, 2023)
Pantry Feeder reconfiguration at the Cipinang substation requires readjusting its relay parameters so it can work fast, selectively, and sensitively. The conventional relay parameter calculation method requires a manually iterative process, which may result in inaccuracy. To avoid this error, the parameters of the main relay (Relay CBO E146) and the backup relay (Relay Incoming Feeder) at the Pantry Feeder are set using the metaheuristic method, in this case the Firefly Algorithm. This algorithm's goal is to find the shortest relay coordination time given the relay working time limits and coordination time intervals. The optimization results obtained were validated using the ETAP application and compared with the results of conventional parameter calculation at four different fault points. The Firefly algorithm method can produce faster yet still selective relay coordination with a coordination time interval are 0.273; 0.349; 0.389; 0.456 seconds, while the conventional method is 1.072; 1.162; 1.302; 1.482 seconds.